AlGaInP optical source integrated with fiber links and silicon avalanche photo detectors in fiber optic systems - Mahmoud M. A. Eid; Shabana Urooj; Norah Muhammad Alwadai; Ahmed Nabih Zaki Rashed (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
This study has clarified aluminium gallium indium phosphide (AlGaInP) optical source integrated with fiber links and silicon avalanche photodetectors in fiber optic systems. The output spectral power, rise time, signal frequency and resonance frequency for AlGaInP laser diode. The laser diode rise time, output spectral power and resonance/signal frequencies versus injection current and ambient temperatures are sketched. The silica doped germanium fiber link pulse broadening and the signal fiber bandwidth are investigated against temperature variations. The signal per noise ratio is related to Q value and bit error rate (BER) at the receiving point (Si avalanche photodetector (APD)) are sketched with temperature.